Spectrum of Hematological Disorders on Bone Marrow Aspiration - An Experience in a Tertiary Care Center - Chhavi Gupta; Ameet Kaur; Subhash Bhardwaj (Dr. Annil Mahajan, 2023)
Background: Hematological disorders are quite frequent in all age groups. Bone marrow aspiration is a relatively safe procedure done for the diagnosis and management of hematological disorders. Aims and Objectives: The present study aimed to evaluate the spectrum of various hematological disorders diagnosed on bone marrow aspiration. Material and Methods: It was a one-year observational study conducted in the hematology section of Department of Pathology, Govt. Medical College, Jammu. Bone marrow aspirations were performed, smears were prepared, stained with Giemsa stain and examined under microscope. Bone marrow findings were noted. Results: Of 323 cases, 166 (51%) were males and 157 (49%) were females. Mean age was 37.9 years with range of 5 months to 85 years. Various disorders seen were megaloblastic anemia (89,27.5%), dual deficiency anemia (27,8.4%), erythroid hyperplasia (50,15.5%), hypoplastic marrow (11,3.4%), acute leukemia (46,14.2%), chronic lymphoproliferative disorder (13, 4.0%), chronic myeloid leukemia (21, 6.5%), ITP (14, 4.3%), myelodysplastic syndrome (4,1.2%), plasma cell dyscrasia (9,2.8%), leishmaniasis (1,0.3%), metastatic malignancy (1,0.3%). Megaloblastic anemia was the most common bone marrow diagnosis. Acute leukemia was the most frequently diagnosed hematological malignancy. Conclusion: Bone marrow aspiration remains an important tool in the diagnosis of wide range of hematological disorders.